ASPECTS OF TOWN MARKETING MANAGEMENT BY TERRITORIAL SELF-GOVERNMENTS - Ulasiuk, Yuliya (Management and Administration Journal, 2022)
This study emphasizes the importance of town marketing management and the key role of self-government bodies in it. The author also points out the specifics of territorial marketing in the management of a town, as well as the problems that Polish local self-governments currently face in building the image and increasing the attractiveness of towns. A survey was conducted among the students of the preparatory courses of the University of Natural Sciences and Humanities of Siedlce, who presented their opinion concerning the university and the town as a potential place for future study, work and residence. The results of the study were analysed statistically and then the conclusions were drawn. The survey shows that the respondents highly appreciate the University, but at the same time, they do not associate their future with the town of Siedlce, arguing that the town is unattractive and unpromising for them. It has been concluded that local self-governments need to use territorial marketing tools to increase the attractiveness of the town and positioning it on the competitive field.